Clinical, Immunological, and Molecular Findings in Five Patients with Major Histocompatibility Complex Class II Deficiency from India - Aluri, Jahnavi; Gupta, Maya; Dalvi, Aparna; Mhatre, Snehal; Kulkarni, Manasi; Hule, Gouri; Desai, Mukesh; Shah, Nitin; Taur, Prasad; Vedam, Ramprasad; Madkaikar, Manisha (Frontiers in Immunology, 2018)
Major Histocompatibility Complex (MHC) class II deficiency is a rare autosomal recessive form of primary immunodeficiency disorder (PID), characterized by the deficiency of MHC class II molecules. This deficiency affects the cellular and humoral immune response by impairing the development of CD4+T helper(Th) cells and Th cell-dependent antibody production by B cells. Affected children typically present with severe respiratory and gastrointestinal tract infections. Hematopoietic Stem Cell Transplantation (HSCT) is the only curative therapy available for treating these patients. This is the first report from India wherein we describe the clinical, immunological, and molecular findings in 5 patients with MHC class II deficiency. All patients presented with recurrent lower respiratory tract infection as the most common clinical presentation within their first year of life and had a complete absence of HLA-DR (Human Leukocyte Antigen–antigen D Related) expression on B cells and monocytes. Molecular characterization revealed novel mutations in RFAXP, RFX5 and CIITA genes. Despite genetic heterogeneity, these patients were clinically indistinguishable. Two patients underwent HSCT but had a poor survival outcome. Detectable level of T cell receptor excision circles (TRECs) were measured in our patients, highlighting that this form of PID may be missed by TREC based newborn screening program for Severe Combined Immunodeficiency (SCID).